Transmembrane Domain 3 (TM3) Governs Orai1 and Orai3 Pore Opening in an Isoform-Specific Manner - Tiffner, Adéla; Maltan, Lena; Fahrner, Marc; Sallinger, Matthias; Weiß, Sarah; Grabmayr, Herwig; Höglinger, Carmen; Derler, Isabella (Frontiers in Cell and Developmental Biology, 2021)
STIM1-mediated activation of calcium selective Orai channels is fundamental for life. The three Orai channel isoforms, Orai1-3, together with their multiple ways of interplay, ensure their highly versatile role in a variety of cellular functions and tissues in both, health and disease. While all three isoforms are activated in a store-operated manner by STIM1, they differ in diverse biophysical and structural properties. In the present study, we provide profound evidence that non-conserved residues in TM3 control together with the cytosolic loop2 region the maintenance of the closed state and the configuration of an opening-permissive channel conformation of Orai1 and Orai3 in an isoform-specific manner. Indeed, analogous amino acid substitutions of these non-conserved residues led to distinct extents of gain- (GoF) or loss-of-function (LoF). Moreover, we showed that enhanced overall hydrophobicity along TM3 correlates with an increase in GoF mutant currents. Conclusively, while the overall activation mechanisms of Orai channels appear comparable, there are considerable variations in gating checkpoints crucial for pore opening. The elucidation of regions responsible for isoform-specific functional differences provides valuable targets for drug development selective for one of the three Orai homologues.